Stress and strain concentration at a circular hole in an infinite plate - Stowell, Elbridge Z. (National Advisory Committee for Aeronautics, 1950)
Formulas for stress and strain concentration at a circular hole in an infinite plate under tension have been derived for use in the plastic region. Values of stress concentration obtained from the formula are in good agreement with limited tests on 24S-T3 aluminum-alloy tension panels. The strain concentration factor is also in agreement with these tests.
"April 1950."
NACA TN No. 2073.
Keywords: Plates (Engineering); Holes.; Strains and stresses.; elektronické knihy; electronic books